PENGARUH ARUS KAS OPERASI, LEVERAGE, PROFITABILITAS DAN ENTERPRISE RISK MANAGEMENT (ERM) DISCLOSURE TERHADAP FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Heni Yusnita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This research was conducted to determine the effect partially or simultaneously between operating cash flow, leverage , profitability and enterprise risk management on financial distress in manufacturing companies in the basic industry and chemical sector listed on the Indonesia Stock Exchange for the 2018-2020 periods. The data analysis technique used is quantitative research methods with descriptive and verification approaches. The type of data used is secondary data obtained from the Indonesia Stock Exchange (BEI). The method of determining the sample of this study using purposive sampling. The population in this study were 78 companies. Companies that meet the criteria to be sampled in this study are 19 companies.The results of the study partially show that operating cash flow and enterprise risk management disclosure have a significant effect on financial distress. Meanwhile, leverage and profitability do not have a significant effect on financial distress. While simultaneously operating cash flow, leverage , profitability and enterprise risk management disclosure have a significant effect on financial distress.